Enhanced abrasion resistance of coated particleboard pre-treated with atmospheric plasma : Pojačana otpornost na abraziju premazanih iverica prethodno obrađenih atmosferskom plazmom - Žigon, Jure (Array, 2020)
This study aims to investigate the influence of atmospheric plasma treatment on the abrasion resistance of particleboards, as an example of a wood-based material, coated with a waterborne finish. The treatment of the substrate, prior to coating application, using a floating-electrode dielectric barrier discharge (FE-DBD) plasma, resulted in an enhanced abrasion resistance of the coated particleboards in comparison to the untreated ones during the abrasion test with a duration of 200 revolutions. This finding was related to lower contact angles of water and coating after treatment with plasma and greater hardness of the coating on the treated substrates. The micrographs of the sample cross sections recorded with scanning electron microscope showed differences in the amounts of remained coating on the abraded areas. Investigation with attenuated total reflection Fourier transform infrared spectroscopy revealed that treatment of the substrate with plasma did not affect the chemical composition nor the curing and structure of the later applied coating. Further studies should be performed to determine the resistance properties of such surface systems to other impacts.